Explicit and implicit stock investment: Differences in psychological characteristics and risky behavior between college students majoring in financial engineering or business - Park, Junsu; Kim, Do Yeong; Oh, Semi (Current Psychology, 2020)
This study (a) investigates dispositional attributes regarding the risk-related personality, attitude, and behavior of college students majoring in financial engineering (FE-major group) and business (business-major group); and (b) examines whether risky behavior is differentially explained by explicit versus implicit attitude toward stock investment. The FE-major group scored consistently higher than the business-major group on measures of sensation-seeking, financial risk-taking, and computerized risk-taking behavior. This pattern was also observed in the two explicit attitudinal measures of risk, whereas no group differences were noted on the two corresponding implicit measures of risk. A newly developed implicit measure of stock investment showed incremental validity in predicting risky behavior beyond the corresponding explicit measure.
Keywords: Explicit and implicit risk attitude; Financial engineering; Personality; Risk; Risky behavior; Stock investment